Impact of Single Blast Exposure on Neuronal Damage and Protein Levels in the Rat Brain at Varying Pressures - Bansal, Puru; Bhat, Dhananjaya I.; Jain, Chirag; Subramaniam, Sarada; Mahadevan, Anita; Shukla, Dhaval; Devi, Bhagavatula Indira (Indian Journal of Neurotrauma, 2024)
Brain injuries from blasts are increasingly common in both civilian and war settings. The impact of blast injuries at different pressure levels remains unclear, and their long-term effects are not well understood. This study investigates how varying blast pressures affect the rat brain over time.Forty adult Sprague-Dawley rats were randomized into four groups of 10. Three groups were exposed to blasts, while one served as a control and was only subjected to blast sounds. Each group received a single blast at different pressures, followed by neuropsychological tests. After 28 and 84 days, the rats were sacrificed to measure tau protein and acetylcholine esterase levels and to conduct histological examinations of brain tissues.A single blast exposure did not significantly impact visuospatial memory or recall. Despite the lack of noticeable cognitive deficits, histopathological and biochemical analyses revealed reduced tau protein levels, indicating ongoing neuronal damage.While a single blast did not significantly impair visuospatial memory or recall in this rat model, there were decreases in tau protein and acetylcholine esterase levels, along with histological signs of neuronal damage.
Keywords: blast injury; traumatic brain injury; acetylcholinesterase; rat model; tau; visuospatial memory